ANALISIS KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN KOMPAS 100 PERIODE 2014-2017 - Siti Khusnul Khotimah (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
Firm value is essentially a reflection of investor confidence in the company. If the company's value is good, it will be viewed by potential investors as good, so that it will attract potential investors to invest in the company and vice versa, if the implied company value is not good, then potential investors will rate the company with a low value so that potential investors are not interested in the company. According to Rinyana, et al., (2016) High company value is the desire of company owners, because high values indicate the prosperity of shareholders. This study aims to examine the effect of investment decisions (PER), funding decisions (DER) and profitability (ROE) partially and simultaneously on the firm value of the company Kompas 100 on the Indonesia Stock Exchange 2014-2017 period.Samples collection method in this study is purposive sampling. The sample in this study consisted of 60 companies and were analyzed using SPSS version 24 software. This study used an associative causal method (cause-and-effect) with a quantitative approach and the data used were secondary data from the financial statements of the company Kompas 100 listed on the IDX. during the period 2014-2017. Data testing techniques used in this study include classical assumption test, correlation test, regression test, coefficient of determination. Furthermore, testing the hypothesis using the, t test and F test.The results of the analysis show that the variable Price Earning Ratio (PER) has a tcount of (15.28170) > t table (1.653) and a significant value (0.000 <0.05), which means that Price Earning Ratio (PER) has a significant effect on Firm Value at the company Kompas100. The variable Debt to Equity Ratio (DER) has a tcount of (2.03314) > t table (1.653) and a significant value (0.04334 <0.05), which means that the Debt to Equity Ratio (DER) has a significant effect on Firm Value at Kompas100. The variable Return On Equity (ROE) has a tcount of (18.21267) > t table (1.653) and a significant value (0.000 <0.05), which means that Return On Equity (ROE) has a significant effect on Firm Value at the Kompas100 company. From testing all independent variables simultaneously, it is obtained that the value of F count is 237,887 > F table of 3.040, which means Price Earning Ratio (PER), Debt to Equity Ratio (DER), and Return On Equity (ROE) together have a significant effect on Firm Value in companies in the Kompas 100 Index listed on the IDX in 2014-2017. The study concluded that variables PER, DER and ROE partially have a positive and significant effect on Firm Value. Simultaneously, the variables PER, DER and ROE together have a significant effect on Firm Value.